Endometrial Flushing Tumor Necrosis Factor Alpha and Interleukin 2 Levels in Women with Polycystic Ovary Syndrome, Leiomyoma and Endometrioma: Comparison with Healthy Controls - Demir, Mustafa; Kalyoncu, Senol; Ince, Onur; Ozkan, Bulent; Kelekci, Sefa; Saglam, Gulcan; Sutcu, Recep; Yilmaz, Bulent (Geburtshilfe und Frauenheilkunde, 2019)
Introduction An important open question in the literature is whether endometrial receptivity marker levels are different in infertility related diseases than healthy women. The aim of the study is to compare the levels of interleukin two (IL-2) and tumor necrosis factor alpha (TNF-α) during the implantation window in the endometrial flushing fluid of polycystic ovary syndrome (PCOS), endometrioma, leiomyoma patients with healthy controls.Material and Methods In this case control study, after obtaining endometrial flushing fluids at mid-luteal phase of ovulatory women with PCOS (n = 20), endometrioma (n = 19), leiomyoma (n = 20) and healthy controls (n = 20), IL-2 and TNF-α levels were measured using ELISA kits in BioTek ELISA devices.Results Mean TNF-α levels (ng/mL) were similar for the PCOS (305.6, p = 0.220) and the leiomyoma group (246.3, p = 0.502) compared to healthy patients (261.1). However, the levels were higher in the endometrioma group (338.2, p = 0,004) than the control group (261.1) in a statistically significant way. Mean IL-2 levels (ng/mL) were significantly lower in the PCOS (290.9, p = 0.0005), the leiomyoma (282.9, p = 0.0002) and the endometrioma patients (229.5, p = 0.0009) than the control group (416.0).Conclusion Relative to the control group, endometrial flushing fluid TNF-α levels were significantly higher in endometrioma patients and IL-2 levels were significantly lower in PCOS, leiomyoma and endometrioma patients. In benign gynecological diseases, endometrial markers related to infertility seem to show differences in endometrial flushing fluid. Future studies might identify the reference values for these markers, and endometrial markers can be used to diagnose gynecologic disorders causing infertility.
Keywords: endometrial receptivity; interleukin 2; tumor necrosis factor alpha; polycystic ovary syndrome; leiomyoma; endometrioma